EFFECT OF SUPERVISION, MOTIVATION OF ACHIEVEMENT AND REWARD TO TEACHER PERFORMANCE WITH LEADERSHIP STYLE AS VARIABLES OF MODERATION - Muzakki Hidayat; Muhaimin Dimyati; Supardi Supardi (STIE Mandala Jember, 2018)
Supervision is one form of attention of the principal to the teacher in addition of giving rewards that can foster motivation of achievement that will give effect to the performance of teachers. If it supported by a leadership style, it will be able to improve teacher performance. This study aims to determine and analyze the influence of supervision, achievement motivation and reward on the performance of teachers and the influence of moderation leadership style on supervision, achievement motivation and reward on teacher performance. This research is a survey research conducted in Al Baitul Amien 02 Jember elementary school with sampling technique using total sampling technique, so that the sample obtained 40 respondents. Hypotheses were tested using multiple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that supervision, achievement motivation and reward on teacher performance either simultaneously or partially. Leadership style has not been able to moderate the influence of supervision, achievement motivation and reward on teacher performance. Keywords: Supervision, Achievement Motivation, Rewards, Performance, Leadership Style